2016
DOI: 10.1021/acs.jafc.6b03140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preharvest Sprouting of Wheat (Triticum aestivum) in the Field on Starch, Protein, and Arabinoxylan Properties

Abstract: To obtain detailed knowledge on possible changes in the properties of starch, proteins, and arabinoxylan as a result of field preharvest sprouting (PHS), three wheat varieties were harvested at maturity and several weeks later when severe PHS had occurred. Falling number values of flour dropped from 306 to 147 s (Sahara), 382 to 155 s (Forum), and 371 to 230 s (Tobak). Blocking of α-amylase activity demonstrated that the decline in falling number and changes in RVA pasting and gelation properties were not caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 12 publications
4
40
0
Order By: Relevance
“…Silver nitrate strongly inhibits the α-amylase activity during the RVA test, no effect on other flour components are known today, but cannot be excluded definitely. [10] As expected, for freshly milled flour higher viscosities were found after AgNO 3 addition compared to the results with water as a solvent. Variations within the different flours were lower, as PV varied from 2414 to 2533 cP, TV from 1550 to 1610 cP, and FV from 2604 to 2756 cP.…”
Section: Storage-induced Changes In Wheat Flour Pasting Propertiessupporting
confidence: 61%
See 3 more Smart Citations
“…Silver nitrate strongly inhibits the α-amylase activity during the RVA test, no effect on other flour components are known today, but cannot be excluded definitely. [10] As expected, for freshly milled flour higher viscosities were found after AgNO 3 addition compared to the results with water as a solvent. Variations within the different flours were lower, as PV varied from 2414 to 2533 cP, TV from 1550 to 1610 cP, and FV from 2604 to 2756 cP.…”
Section: Storage-induced Changes In Wheat Flour Pasting Propertiessupporting
confidence: 61%
“…With the addition of silver nitrate solution (Table ), a similar behaviour was identified, but changes were less pronounced and some remarkable differences were found. Silver nitrate strongly inhibits the α‐amylase activity during the RVA test, no effect on other flour components are known today, but cannot be excluded definitely . As expected, for freshly milled flour higher viscosities were found after AgNO 3 addition compared to the results with water as a solvent.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Amylases produced during germination break glycosidic linkages of starch to produce single sugars (maltose, glucose, and dextrin) . Moreover, according to Olaerts et al, wheat germination affects starch pasting properties; it reduces the binding capacity and swelling power of starch in water. Simsek et al also reported that wheat germination induces significant changes in the physiochemical properties of starch due to α‐amylase activities, which contributes to degradation of starch molecules.…”
Section: Introductionmentioning
confidence: 99%